An Overview on Actual Knowledge About Immunohistochemical and Molecular Features of Vitality, Focusing on the Growing Evidence and Analysis to Distinguish Between Suicidal and Simulated Hanging - Maiese, Aniello; Del Duca, Fabio; Santoro, Paola; Pellegrini, Lavinia; De Matteis, Alessandra; La Russa, Raffaele; Frati, Paola; Fineschi, Vittorio (Frontiers in Medicine, 2022)
In forensic practice it is often asked to the pathologist to determine whether a hanging was committed as a suicide or as a simulated hanging (when a dead body is suspended after death). When exterior evidences of violence are absent and the crime scene investigation fails to identify useful proofs, it's nearly impossible to tell whether the dead body was suspended or not. As a result, determining whether the ligature mark was created during life or not should rely on the research and demonstration of vital reactions on ligature mark. The main purpose of this review article is to provide a summary of current knowledge about the histological and immunohistochemical characteristics of vitality in hanging. Authors also aim to identify the most significant vitality markers on ligature mark for further scientific validation and to propose a standardized diagnostic protocol for hanging. The study was conducted according to PRISMA Protocol (Preferred Reporting Items for Systematic Review). Relevant scientific papers were found from PubMed up to April 2021, using the following keywords: hanging AND skin AND vitality. Three main points were studied: ligature mark dehydration, immunological response to mechanical injury, and apoptosis induction as a result of the previous points. An increase in apoptosis is evident in the ligature mark (due to physical and chemical processes involved), as demonstrated by FLIP depletion. Immunohistochemical detection of AQP3 and increase in concentration of different electrolytes rely solely on ligature mark dehydration. Also, MiRNAs could become reliable forensic biomarkers for ligature mark vitality diagnosis in the near future. To ensure high reliability in court cases, forensic investigation in hanging should rely on modern and proven markers, even a mix of several markers.